LARANGAN RIBA DITINJAU DARI TAFSIR AYAT AHKAM SURAT AL-BAQARAH AYAT 275-281 - Itsnaini Chusnul Khotimah (Al-Iqtishad: Jurnal Ekonomi Syariah, 2022)
The practice of usury has become a habit in people's daily lives. Both from implied usury and real usury. Even though the prohibition of usury exists in all divine religious rules. In Islam, the prohibition of usury is clearly stated in the Quran. Among them are in the letter Al-Baqarah Verses 275 to 281. Apart from the practice of usury, it also has a bad impact on people who practice it. The purpose of this study is to determine for sure the prohibition of Riba in the Qur'an through Tafsir Ayat Ahkam. The methodology used is descriptive qualitative methodology with a literature study approach. The results obtained from this study are additional knowledge regarding the prohibition of usury in detail through the interpretation of the ahkam verse.